Pharmaceutical promotion : the theoretical framework of regulation. - Othman, Noordin; Vitry, Agnes I.; Roughead, Elizabeth E. (IIUM Press, 2011)
Pharmaceutical promotion IS persuaSIve communication (World Health Organization, 2010) which often creates the impression of superior efficacy of a medicine, \vithout a\vareness of the health professionals (Mansfield & Henry, 2004). Doctors often use pharmaceutical promotion as a source of medicines information (Fischer et a1., 2009~ McKinney et aI., 1990~ National Survey ofPhysicians (2002), Poirier et aI., 1994; Prosser et a!., 2003 ~ Strang et aI., 1996; Uchenna et aI., 2010) and it may influence their prescribing pattern (Andersen et aI., 2006~ Muijrers et aI., 2005). For this reason, it is essential that the medicines information provided in pharmaceutical promotion should be effectively regulated